MODEL PEMBELAJARAN VOLI BERBASIS PERMAINAN UNTUK MENINGKATKAN MOTIVASI BELAJAR PJOK SISWA SD - Eriek Satya Haprabu; Jasmani; Nico Ponco Sulistyo; Messi Dwiandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this research is to create a game-based volleyball learning model that can enhance elementary school students' motivation to learn Physical Education, Sports, and Health (PJOK). This study was conducted using the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. This study was conducted at SDN Purworejo and involved elementary school students and PJOK teachers. Learning motivation questionnaires, interviews, observations, expert validation sheets, and teacher and student response questionnaires are all methods used to collect data. To assess the validity and practicality of the product, data analysis uses descriptive statistics. Meanwhile, the effectiveness of the model was evaluated using a paired sample t-test. The research results show that the developed learning model has an average validity of 93.23% with a very valid category; the practicality test shows a positive response from teachers of 96.2% and students of 94.5%, indicating that the model is very practical to apply in PJOK learning. Additionally, the implementation of the model shows a significant increase in students' desire to learn, as evidenced by an increase in student motivation scores of 67.25. Game activities can make learning more active, enjoyable, and collaborative, and increase student engagement during the learning process. The results of this study indicate that the game-based volleyball learning model can be used as an alternative for new innovations in PJOK learning in elementary schools. This model enhances students' desire to learn and also helps implement a learner-centred approach to education.